Dynamic Functional Assessment of Hand Motion Using an Animation Glove: The Effect of Stenosing Tenosynovitis. (November 2018) - Schreck, Michael J.; Kelly, Meghan; Lander, Sarah; Kaushik, Anjan; Smith, Heather; Bell, Scott; Raman, Vishwanath; Olles, Deana; Geigel, Joe; Olles, Mark; Elfar, John C.
Background: The aim of the present study is to determine whether an animation glove can be utilized to provide a reliable and reproducible assessment of dynamic hand function and whether this assessment is altered in the setting of hand pathology.Methods: Ten subjects without known hand pathology and 11 subjects with known stenosing tenosynovitis were assessed on tasks involving hand function at varied speeds, including forceful and gradual making of a fist and the quick and slow grip of a baseball using an animation glove to record range of motion and measures of velocity (CyberGlove II).Results: In normal subjects, peak extension and flexion velocity of the index and middle finger was highest in the metacarpophalangeal and lowest in the distal interphalangeal; however, the converse was true in the ring finger. In those subjects with stenosing tenosynovitis, the animation glove was able to detect a triggering event during assessment. Furthermore, there was a significant decrease in the maximum velocity of the proximal interphalangeal joint observed with the slow fist task in both flexion and extension (55%, P < .01) in the affected hand when compared with the unaffected hand.Conclusions: The CyberGlove II can be utilized in the dynamic functional analysis of the hand and is able to detect a triggering event in subjects with known stenosing tenosynovitis. Those subjects demonstrate a significant decrease in maximum velocity in slow fist tasks, highlighting the need for comprehensive assessment to ascertain the full extent of functional limitations that can occur in the setting of hand pathology.